Fundamental solution of the Cauchy problem for the Shilov-type parabolic systems with coefficients of bounded smoothness - Litovchenko, V. A.; Unguryan, G.M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Under the condition of minimal smoothness of the coefficients, we construct the fundamental solution of the Cauchyproblem and study the principal properties of this solution for a special class of linear parabolic systems with boundedvariable coefficients covering the class of Shilov-type parabolic systems of nonnegative kind.